2015
DOI: 10.1016/j.virol.2015.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Escape of non-enveloped virus from intact cells

Abstract: How do viruses spread from cell to cell? Enveloped viruses acquire their surrounding membranes by budding. If a newly enveloped virus has budded through the plasma membrane, it finds itself outside the cell immediately. If it has budded through the bounding membrane of an internal compartment such as the ER, the virus finds itself in the lumen, from which it can exit the cell via the conventional secretion pathway. Thus, although some enveloped viruses destroy the cells they infect, there is no topological nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 30 publications
(39 reference statements)
1
54
0
Order By: Relevance
“…In a recent review article [32], Bird and Kirkegaard proposed three alternative mechanisms capable of sustaining non-lytic egression of naked viruses. Our TEM data clearly argues against first proposed mechanism, the blebbing of virus particles from the PM of infected cells, for the release of IBDV virions.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review article [32], Bird and Kirkegaard proposed three alternative mechanisms capable of sustaining non-lytic egression of naked viruses. Our TEM data clearly argues against first proposed mechanism, the blebbing of virus particles from the PM of infected cells, for the release of IBDV virions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we showed that these compartments contain autophagy protein LC3, indicating a potential role for a cellular autophagy pathway in nonlytic viral release. The subversion of the autophagy pathway by animal nonenveloped viruses has been extensively studied (9,10). Given that the autophagy pathway is a cell clearance mechanism, it comes as a surprise that rice reoviruses have evolved to subvert such cellular process for viral nonlytic release.…”
Section: Autophagy and Apoptosismentioning
confidence: 99%
“…The general belief that non-enveloped viruses are exclusively released as a consequence of cell lysis (Fig. 1D) has recently been challenged [62]. HepA, HepE, and poliovirus were shown to escape from intact cells by acquiring a temporary membrane (Fig.…”
Section: Transmission Of Non-enveloped Virusesmentioning
confidence: 99%